Analisis Komparatif Kinerja Keuangan BPRS Linkage Program dan Non Linkage Program Periode 2014-2015 - Allen Anandika Rizky Pratama; Achsania Hendratmi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This research aims to discover whether there are any differences in financial performance between BPRS which take part in the linkage program and the one which do the contrary, in period of 30 March 2014 – 30 December 2015. The method used in this research is quantitative where the research is done by doing a descriptive statistical analysis and inferential statistic. The comparison of the financial performances are based on financial ratio assessment consisting of CAR, NPF, ROA, BOPO and FDR. Research shows that there are indeed found differences in financial performance between BPRS which take part in the linkage program and the one which do the contrary. Differences in financial performance viewed from financial ratio of FDR, NPF and CAR. However, earning ratio (rentabilitas)ROA and BOPO not possessed any differences between BPRS which take part in the linkage program and BPRS which does not.